A Pioneer Woman. - Ross, Michael (Communications of the ACM, 2009)
The article reports that computer programmer Jean Bartik was inducted into the Computer History Museum's Hall of Fellows. Bartik had no interest in a classroom career when she graduated from college in 1945, the article states. Topics include her work in programming the first general-purpose computer, ENIAC (Electronic Numerical Integrator and Computer), her work in calculating artillery trajectories, and setting ENIAC's switches and cables to ensure ENIAC's correct functioning. Also discussed is Bartik's work in converting ENIAC into a stored program computer.